Small-scale Biogas by Lake Victoria - Hagegård, Karolina (My University, 2009)
This study is a step on the way to try and introduce small-scale biogas, mainly as cooking fuel, into the poor rural areas around Lake Victoria, in East Africa. It deals with the conditions for doing so, and the possible effects thereof. Some different feed materials are presented: Water hyacinth, wild sunflower, cow dung and human faeces. Using human faeces can have good effects on public health, since the biogas process hygienizes the faeces to a large extent. A biogas digester was built at a secondary school in Kenya. It cost around 200 euro, including insulation with clay-straw. There was no skilled labour involved, and it was concluded that this type of digester (although this one leaked by the end of the project time) could well be suitable for the, mostly poor, people around Lake Victoria, to build and use. The aim is that once the first digester is up and running, the technology will spread from user to user. The constructed digester is estimated to be able to replace around 40 % of the present cooking fuel needs, and the full fertilizer needs, for a family of 5. If the family at present has to pay for cooking fuel, this means that they will have their investment back in around 200 days of using the digester. Future development may yield even better results. Finally there is a chapter with some recommendations for how to spread the technology in this kind of area. The most important recommendation is to make sure that there is a genuine interest from the users. Subsidies are advised to be used with care, or not at all, since it tends to work against a genuine commitment. Other recommendations are thorough education, and accessible technical support.
Keywords: Biokemisk och bioteknisk processteknik; Biochemical process engineering